Establishment and characterization of a rat intestinal microvascular endothelial cell line. (October 2021) - Liu, Ping; Bian, Yifei; Zhong, Jia; Yang, Yang; Mu, Xiang; Liu, Zhongjie
Highlights: Intestinal microvascular endothelial cell is a fundamental component of the gut-vascular barrier. A novel rat intestinal microvascular endothelial cell line, RIMVEC-11, was established. RIMVEC-11 shows potentials of tube formation and cell migration. Abstract: Intestinal microvascular endothelial cell (IMVEC) is a fundamental and essential component of gut-vascular barrier which is closely associated with intestinal disorders However, there is still a lack of established intestinal microvascular endothelial cell line. In the present study, a newly established rat intestinal microvascular endothelial cell line termed RIMVEC-11 was described and characterized which has been stably cultured for more than 90 passages so far. RIMVEC-11 was characterized by endothelial features with the cobblestone morphology under light microscopy, the Weibel-Palade body and rich vesicles in the cytoplasm on the ultrastructural level, and positive endothelial specific markers CD31 and von Willebrand factor by immunocytochemistry analysis. Meanwhile, RIMVEC-11 maintained the fundamental physiological function of the microvascular endothelial cells. Tube formation assay confirmed that RIMVEC-11 retained the potential for capillaries formation. Scratch assay confirmed the endothelial cell migration potential of RIMVEC-11. Thus, a novel IMVEC cell line RIMVEC-11 was established, which could be used as a promising model for the gut-vascular barrier research.